1996
DOI: 10.1002/elan.1140081106
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric and amperometric studies of selected thiols and dimethyldisulfide using a screen‐printed carbon electrode modified with cobalt phthalocyanine: Studies towards a gas sensor

Abstract: Cyclic voltammetry was used to investigate the electrochemical behavior of hydrogen sulfide, methanethiol, ethanethiol and dimethyldisulfide at a cobalt phthalocyanine modified screen-printed carbon electrode (SPE) in phosphate electrolytes of different pH values. The thiols and hydrogen sulfide were found to undergo electrocatalytic oxidation while dimethyldisulfide exhibited an electrocatalytic reduction reaction. These processes were considered to involve the central cobalt(ii) ion in the phthalocyanine mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…During the last decade, several authors [5][6][7][8][9][10][11][12][13][14][15][16][17] have reported the catalytic electrooxidation of various thiols on electrodes modified with metallophthalocyanines. In general, electrodes of this type can be used as sensors [15][16][17][18][19][20][21][22][23][24][25] and various configurations have been developed such as carbon paste [15][16][17] and screen-printed carbon electrodes [19][20][21][22][23][24][25] containing cobalt phthalocyanines and derivatives. The advantage of the reported cobalt phthalocyanine-based electrodes is that the thiols (namely 2-mercaptoethanol, L-cysteine, reduced gluthathione etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, several authors [5][6][7][8][9][10][11][12][13][14][15][16][17] have reported the catalytic electrooxidation of various thiols on electrodes modified with metallophthalocyanines. In general, electrodes of this type can be used as sensors [15][16][17][18][19][20][21][22][23][24][25] and various configurations have been developed such as carbon paste [15][16][17] and screen-printed carbon electrodes [19][20][21][22][23][24][25] containing cobalt phthalocyanines and derivatives. The advantage of the reported cobalt phthalocyanine-based electrodes is that the thiols (namely 2-mercaptoethanol, L-cysteine, reduced gluthathione etc.)…”
mentioning
confidence: 99%
“…In this work, we combine for the first time the use of electrochemically formed polypyrrole-doped cobalt tetrasulfonated phthalocyanine (CoTSPc) with ultramicro-carbon-fiber electrode configuration (UMCF) to achieve the electrocatalytic oxidation of 2-mercaptoethanol (2-ME) in alkaline aqueous solution and provide a miniaturized electrochemical sensor that is easily fabricated from low cost materials, providing an ultramicroprobe that may be developed for applications in biological systems. We have selected 2-ME as the examined analyte target since its electrochemistry is well developed in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18]25].Electrochemical formation of polypyrrole-doped CoTSPc on UMCF was performed by anodic oxidation of 1 mM CoTSPc tetrasodium salt þ0.1 M pyrrole in aqueous solution by one potential scan between À0.2 and 0.7 V, at room temperature, starting at the lower potential limit. The incorporation of CoTSPc within the polypyrrole matrix (PPy) is based on the ion exchange properties of the oxidized polymer [26]: the multianionic tetrasulfonated cobalt phthalocyanine molecules are introduced into polypyrrole film as counterions (or ''doping'' ions) during the electrochemical growth of the polymer matrix.…”
mentioning
confidence: 99%
“…Today, the most popular method for the quantitative analysis of sulfur compounds in environmental samples relies on gas chromatography (GC) [57][58][59]. However, GC analysis of VSCs requires efficient sample pretreatment and enrichment methods, and such procedures are complicated, time consuming, and tedious [60][61]. In contrast, electrochemistry has much higher sensitivity, much lower detection limits, and lower cost.…”
Section: Applications In Batteries and Electrochemistrymentioning
confidence: 99%
“…It is possible to extend many applications in solution phase of these complexes to a solid phase by an immobilization process on an inert matrix surface and by an impregnation or chemical bonding procedures 4 . Complexes immobilized by an impregnation procedure on an inert matrix surface have been used to prepare chemically modified electrodes viewing numerous electrocatalytic reactions [5][6][7][8][9][10][11][12] . Another procedure has been to immobilize the phthalocyanine or porphyrine complexes by a chemical bonding of the central metal atoms to basic groups grafted on solid surfaces [13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%